STRATEGY FOR MADRASA HEADS TO MOTIVATE TEACHERS IN THE TEACHING AND LEARNING PROCESS AT MTS AL-WASHLIYAH PAKAM VILLAGE - Anwar Sazali; Hikmatul Husna Usnur (RADJA PUBLIKA, 2021)
TypeThis research is a type of qualitative descriptive research.The results of the research in this thesis,there are several strategies used by the HeadMTs Al Washliyah Desa Pakam provides motivation to teachers in the teaching and learning process, namely first, instilling discipline, second, setting a good example in terms of speech, clothing, and actions, third, visits to class during class hours, fourth, guiding in making learning devices and overseeing the use of time Study. Obstacles faced by Madrasah Principals inMTs Al Washliyah Pakam Villagein increasing teacher motivation in the teaching and learning process, namely from within the teacher himself such as, there are still teachers who do not want to admit their low quality, especially in class mastery abilities, managing learning programs, and using learning media. Barriers from outside such as learning facilities and infrastructure that are still incomplete. as well as in developing the arrangement of the physical environment of madrasas because the land is limited. Such as the absence of a soccer field, and the lack of books in the library which are materials for students to dig deeper into subject matter.